Regulation of Memory Function by Feeding-Relevant Biological Systems: Following the Breadcrumbs to the Hippocampus - Suarez, Andrea N.; Noble, Emily E.; Kanoski, Scott E. (Frontiers in Molecular Neuroscience, 2019)
The hippocampus (HPC) controls fundamental learning and memory processes, including memory for visuospatial navigation (spatial memory) and flexible memory for facts and autobiographical events (declarative memory). Emerging evidence reveals that hippocampal-dependent memory function is regulated by various peripheral biological systems that are traditionally known for their roles in appetite and body weight regulation. Here, we argue that these effects are consistent with a framework that it is evolutionarily advantageous to encode and recall critical features surrounding feeding behavior, including the spatial location of a food source, social factors, post-absorptive processing, and other episodic elements of a meal. We review evidence that gut-to-brain communication from the vagus nerve and from feeding-relevant endocrine systems, including ghrelin, insulin, leptin, and glucagon-like peptide-1 (GLP-1), promote hippocampal-dependent spatial and declarative memory via neurotrophic and neurogenic mechanisms. The collective literature reviewed herein supports a model in which various stages of feeding behavior and hippocampal-dependent memory function are closely linked.